Theeffect of mining sector determinants on economic growth/ Muhammed Taufiq Mohd Fadi ...[et al.] - Mohd Fadi, Muhammed Taufiq; Hamzah, Munirah Syamimi; Abd Rahman, Nurul Najeha; Wan Yaacob, Wan Fairos (Unit Penerbitan UiTM Kelantan, 2016)
This study aimsto examine the relationship between import and export of miningsectordeterminants representedby the non-metallic, metallic, energy mineral, fertilizer and jewelrysun-sectors towards Malaysia’s Gross Domestic Product (GDP). Data from the year 2001 to 2015 were analyzed. An econometric model was developed usingOrdinary Least Square (OLS) and Unit Root Testwas performed. Result of the study reveals that there is a significant relationship betweenfertilizer import, jewelryimport, energy mineral export and non-metallic exportdeterminantstowards GDP in Malaysia